2020
DOI: 10.3390/cancers12030676
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Clinical Benefit of Radiotherapy in Solitary Plasmacytoma: An International Multicenter Analysis

Abstract: Objective: Although local definitive radiotherapy (RT) is considered the standard of care for solitary plasmacytoma (SP), the optimal RT parameters for SP patients have not been defined. The aim of this retrospective study is to analyze the effectiveness of various RT doses, volumes, and techniques, as well as to define the relevant prognostic factors in SP. Methods: Between 2000 and 2019, 84 patients, including 54 with solitary bone plasmacytoma (SBP) and 30 with extramedullary plasmacytoma (EMP), underwent R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The dose used for our patient was 40 Gy as recommended by the International Lymphoma Radiation Oncology Group. Interestingly, Elsayad et al have shown in their international multicenter analysis that using radiotherapy dose-escalation (above 40 Gy) and modern irradiation techniques as intensity-modulated radiotherapy (IMRT) and proton therapy seem to improve the local control and reduce the rate of relapse in patients with solitary bone or solitary extramedullary plasmacytoma, without a significant effect on survival rates [ 12 ]. Imaging examinations, such as positron emission tomography (PET) computed tomography (CT), are required for the management of suspected SEP, as well as to monitor the therapeutic response to radiotherapy and the possibility of recurrence and progression of into multiple myeloma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dose used for our patient was 40 Gy as recommended by the International Lymphoma Radiation Oncology Group. Interestingly, Elsayad et al have shown in their international multicenter analysis that using radiotherapy dose-escalation (above 40 Gy) and modern irradiation techniques as intensity-modulated radiotherapy (IMRT) and proton therapy seem to improve the local control and reduce the rate of relapse in patients with solitary bone or solitary extramedullary plasmacytoma, without a significant effect on survival rates [ 12 ]. Imaging examinations, such as positron emission tomography (PET) computed tomography (CT), are required for the management of suspected SEP, as well as to monitor the therapeutic response to radiotherapy and the possibility of recurrence and progression of into multiple myeloma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“… 21 In the study by Elsayad including 84 patients with solitary plasmacytoma (including 30 patients with EMP) the addition of systemic therapy improved MM free survival and PFS. 9 Only 4 patients with EMP received systemic therapy thereby rendering a conclusion in EMP patients impossible. The study by Mignot included 46 patients with solitary plasmacytoma (including 6 EMP) treated by either radiotherapy alone or concomitant radiotherapy and systemic therapy with 4 cycles of lenalidomide and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…EMP is highly radiosensitive, and radiation doses above 40-45 Gy are associated with improved survival as compared to lower doses. 2,4,[6][7][8][9] Some centers prefer radiation therapy because of the mutilating procedure of curative surgery. While some studies suggest the benefit of radiation, others show better survival for patients after radical surgery without additional radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with earlier treatment due to localized plasma cell tumor plus evidence of systemic disease were excluded, as these patients are considered to have distinct progression risks. Furthermore, not all of these patients with local plasma cell tumors had received radiotherapy with a dose of more than 40 Gy, which has been shown to be the preferable dose in order to receive complete local remission by a recent study [ 14 ]. This resulted in a baseline-cohort of 147 patients with MRI at initial diagnosis, 52 of which received follow-up wb-MRI and are referred to as follow-up cohort.…”
Section: Methodsmentioning
confidence: 99%